Knowledge, Attitude, and Practice on Arteriovenous Fistula Care Among End‐Stage Kidney Disease Patients Receiving Maintenance Hemodialysis: A Single‐Center, Prospective Cohort Study in Nepal - Santosh Dev; Prajjwol Luitel; Birendra Sah; Bivek Kumar Yadav; Barsha Dev; Ishwor Thapaliya; Kajan Raj Shrestha; Uttam Krishna Shrestha (Health Science Reports)
ABSTRACT Background and Aims The majority of complications arising from the arteriovenous fistula (AVF) site for hemodialysis (HD) can be prevented through the implementation of a daily self‐care plan. This study aimed to assess the knowledge, attitude, and practice (KAP) of hemodialysis patients with end‐stage kidney disease (ESKD) regarding AVF self‐care preoperative, postoperative, and during follow‐up. Methods This prospective cohort study was conducted at a tertiary referral center in Nepal. It included ESKD patients over 18 years with AVF. Patients were interviewed preoperative, postoperative, and at 2, 4, and 6 weeks. KAP was assessed as percentages, and associations were analyzed using the χ2 test. Score comparisons over time used the paired t‐test, with p < 0.05 considered significant. Results Among 173 AVF patients, 98.8% had poor knowledge preoperative, while 98.3% had good knowledge postoperative, with significant improvement in the overall score of knowledge (p < 0.001). Initially, 97.1% were motivated towards self‐care, but this dropped to 78.0% by the 6th week. Most patients practiced weight‐bearing prevention, cleaning, and drying, but fewer practiced daily verification of fluid thrill and exercise with malleable balls. Postoperative knowledge acquisition significantly correlated with male sex and higher socioeconomic status. Conclusion Although the majority of patients undergoing HD planned for AVF exhibited a favorable attitude towards fistula care, their knowledge was poor. Knowledge significantly improved with follow‐ups, but motivation for self‐care decreased over time. Patients' practices generally aligned with knowledge scores, emphasizing the importance of regular reminders and periodic evaluations by healthcare workers for practical aspects of AVF care for all ESKD patients undergoing HD.